STATUS AND ANALYSIS OF RISK DIVERSIFICATION IN COMMERCIAL BANKS (European Journal of Economics, Finance and Business Development, 2025)
The article examines the state and analysis of risk diversification in commercial banks, the main directions of risk diversification in commercial banks at the macroeconomic and microeconomic levels, the possibilities of reducing economic risk associated with risks in banks and preventing financial losses, and the application of the experience of foreign countries in our country.